ISSUE BRIEF EMPLOYMENT DISCRIMINATION AND SMOKER ACCOMMODATION (Tufts Archival Research Center, 2007)
Confidential; Report giving a brief overview of the employment discrimination and smoker accommodation issue. Provides background on the issue, emphasizing the recent increase in discriminatory hiring, firing and promoting practices directed at employees who smoke. Lists proponents and opponents of the tobacco industry's pro-smoking position. States that the industry will act to protect the rights of it's customers, smoking Americans. Provides a legislative history of employment discrimination and smoking accommodation measures that have already been taken in various states. Specifies reasons why it is unacceptable to discriminate against as well as not properly accommodate smoking employees.